Zycie towarzyskie i domowe : nowy savoir-vivre - Rojek, Tadeusz (Warszawa : Ksiazka i Wiedza, 1994)
An up-to-date guide for good manners at home and in social conditions.
Keywords: Poland -- Social life and customs